2015
DOI: 10.1155/2015/327486
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of High-Frequency Transcutaneous Electrical Nerve Stimulation for Dental Professionals with Work-Related Musculoskeletal Disorders: A Single-Blind Randomized Placebo-Controlled Trial

Abstract: Work-related musculoskeletal symptom disorders (WMSDs) have a significant issue for dental professionals. This study investigated the effects of high-frequency transcutaneous electrical nerve stimulation (TENS) on work-related pain, fatigue, and the active range of motion in dental professionals. Among recruited 47 dental professionals with WMSDs, 24 subjects received high-frequency TENS (the TENS group), while 23 subjects received placebo stimulation (the placebo group). TENS was applied to the muscle trigger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…This study aims to evaluate and compare the effectiveness of myofascial release vs high-frequency TENS for pain relief and functional improvement in patients with trapezius myalgia. Myofascial release technique is a soft tissue mobilization technique that is described as the facilitation of mechanical, neural, and psychophysiological adaptive capacity as interfaced through the myofascial system [14]. It works by calming tense muscles while also improving circulation and lymph drainage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study aims to evaluate and compare the effectiveness of myofascial release vs high-frequency TENS for pain relief and functional improvement in patients with trapezius myalgia. Myofascial release technique is a soft tissue mobilization technique that is described as the facilitation of mechanical, neural, and psychophysiological adaptive capacity as interfaced through the myofascial system [14]. It works by calming tense muscles while also improving circulation and lymph drainage.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, such musculoskeletal disorders of neck are usually influenced by prolonged static work posture which leads to few pathophysiological changes in the upper trapezius. Due to physiological changes in the muscle, it leads to elevated anaerobic metabolism and fatigue due to repetitive work [3]. Women are more affected than men, and the prevalence is highest.…”
Section: Introductionmentioning
confidence: 99%
“…(Figure S2b, Table 4). Five studies assessed the effects of ES versus placebo on PPT immediately post-treatment and at short-term follow-up (Hsueh et al, 1997;Maayah & Al-Jarrah, 2010;Rodriguez-Fernandez et al, 2011;Smania et al, 2005;Suh et al, 2015).…”
Section: Electrical Stimulation + Other Intervention Versus Other Interventionmentioning
confidence: 99%
“…One meta-analysis with three studies showed evidence of very low-quality (downgraded by methodological quality, indirectness and imprecision) that TENS increased PPT compared to placebo immediately post-treatment (SMD 0.37, 95% CI 0.05-0.69) (Figure S3) (Maayah & Al-Jarrah, 2010;Rodriguez-Fernandez et al, 2011;Suh et al, 2015) Subgroup analysis according to duration of symptoms showed no differences between groups. (Figure S3a, Table 4).…”
Section: Electrical Stimulation + Other Intervention Versus Other Interventionmentioning
confidence: 99%
“…These wide ranges of frequencies work through various different mechanisms which may influence therapeutic outcomes. For example, in TENS, high-frequency stimulation is thought to inhibit pain according to the gate control theory of pain, while low-frequency stimulation is thought to work through the modulation of opioid receptors, GABA receptors, and serotonin receptors in the periaqueductal gray, rostral ventral medulla, and spinal cord [ 39 , 40 ]. Previous studies that found inconclusive results may have used frequencies that were not therapeutically optimal.…”
Section: Reviewmentioning
confidence: 99%